Sistem pendukung keputusan penentuan penyakit busuk kuncup pada tanaman kelapa sawit dengan metode trend moment di PT. PERKEBUNAN NUSANTARA III (PERSERO) KEBUN AEK NABARA UTARA - Hilman Taufik, Riski Nurjannah; Watrianthos, Ronal; Dalimunthe, Abdul Hakim (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
Oil palm planting has bright prospects due to the sufficient availability of various supporting factors, although there are also various challenges to the existence and sustainability of these natural resources. Oil palm (Elaeis Guineensis Jacq) is a plantation crop that is very tolerant of unfavorable environmental conditions. Bud rot (spear rot) is a disease that attacks the bud or shoot area of oil palm plants. You have to be wary of this disease because it attacks young plants so that the plant grows abnormally, is unable to form fruit, is stunted, and grows slowly. The most worrying thing is that the attack is at the growing point. If a hole is made in the stem, a foul-smelling yellow liquid will come out. The decision support system is a system device capable of solving problems efficiently and effectively, which aims to assist decision making in choosing various decision alternatives which are the result of processing information obtained using a decision making model. Using the Trend Moment method, the aim is to determine the criteria for determining bud rot disease in oil palm plants at PTPN III Aek Nabara Utara.